Power And Mediatic Violence: The Analysis of Özgecan Aslan And Sefika Etik Homicides - Memet ARSLAN (Marmara İletişim Dergisi, 2017)
As a way to guide individual or group behavior; in other words, power as a problem of management and mediatic violence as the power’s one of the ideological apparatuses, violence is represented in the media in various ways. Violence in the media may exist in the news narratives and in the visuals used for news items. The aim of this study is to explain how and by which methods the “Mediatic Violence” is re-produced in the news by the media. This gender – focused violence is far more discursive, literary and textual than the factual. In this framework, critical discourse analysis were conducted on the news items regarding Sefika Etik in Habertürk Newspaper dated 7th of November 2011 and Özgecan Aslan murder report dated 15th of February 2015 in Akşam Newspaper. Findings of these studies show that the mediatic violence which is fictionalized and re-produced in the news, legitimizes violence against women and normalizes it in the public opinion